Circulating T cell atlas in Moyamoya disease: insights into immunopathogenesis of cerebrovascular disorders - Chenglong Liu; Junsheng Li; Siqi Mou; Yuheng Pang; Liujia Chan; Qiheng He; Wei Liu; Zhikang Zhao; Bojian Zhang; Zhiyao Zheng; Wei Sun; Xiangjun Shi; et al. (Journal of Neuroinflammation)
Abstract Background Moyamoya disease (MMD) is a chronic cerebrovascular disorder characterized by progressive stenosis or occlusion of the intracranial arteries, accompanied by the formation of fragile collateral vessels, ultimately leading to ischemic or hemorrhagic strokes. Immune dysregulation, particularly involving T cell abnormalities and mitochondrial dysfunction, plays a critical role in the pathogenesis of MMD; however, their precise relationship remains unclear. Methods Peripheral blood mononuclear cells (PBMCs) from patients with MMD and healthy controls were analyzed using mass cytometry (CyTOF) and transcriptomic profiling. Additionally, clinical characteristics and neuroimaging data were collected to perform integrated correlation analyses with immune profiling data. Results Patients with MMD exhibited aberrant T cell activation and altered subset distribution, accompanied by mitochondrial dysfunction and impaired oxidative phosphorylation capacity. Increased oxidative stress and endoplasmic reticulum stress were observed in T cells, along with disease-specific downregulation of immune checkpoint molecules, including PD-1 and ICOS. Conclusions This study highlights the critical involvement of immune activation and mitochondrial dysfunction in the pathophysiology of MMD, providing novel insights into disease mechanisms and identifying immunometabolic pathways as potential targets for therapeutic intervention.